Recurrence hospitalization due to SARS-CoV-2 infection on human immunodeficiency virus patients - Yaniswari, Ni Made Dwita; Putra, Wayan Wahyu Semara; Laveda, Sandy (International Journal of Advances in Medicine, 2023)
COVID-19 is a global health concern with varying severity. Moderate to severe cases require isolation for 10-20 days, and those with weakened immune systems (like HIV) should isolate for 20 days. Indonesia has a rising number of HIV cases. HIV-positive individuals have a higher risk of COVID-19 and may have lower antibody levels after vaccination. Two case studies of HIV-positive patients who contracted SARS-CoV-2 are presented. In case 1, a 29-year-old patient who received the COVID-19 vaccine and was on antiretroviral therapy was hospitalized three times with worsening symptoms, and unfortunately did not survive. In case 2, a 46-year-old patient with a history of tuberculosis and also on antiretroviral therapy was hospitalized twice, reporting mild symptoms, and did not experience any further symptoms related to COVID-19 after being discharged. Both patients tested positive for COVID-19 using rapid antigen tests and PCR tests and did not report any history of contact with COVID-positive individuals. These case studies highlight the challenges faced by HIV-positive individuals in managing COVID-19, and the need for continued research in this area. Immunocompromised COVID-19 patients need special isolation, even with mild symptoms. Longer isolation periods may be necessary, as studies show positive tests can still mean infectiousness. Viral culture tests can help identify contagious individuals who test positive on PCR tests. People with HIV may need a COVID-19 booster vaccine due to lower antibody levels after the initial vaccine. Further research is needed to develop antiviral treatments for COVID-19 infection in individuals with immunocompromised.